Removal of Cu(II) Ions from Aqueous Solutions by Ferrochrome Ash: Investigation of Mechanism and Kinetics - Ugurlu, Erdogan; Birol, Burak; Gencten, Metin; Bayrak, Yahya (MDPI, 2023)
The release of Cu into water is an immediate concern that negatively affects environmental health. To eliminate this problem, the adsorption of Cu(II) on varying substances has been studied widely for two decades. The utilization of low-cost adsorbents obtained from industrial wastes hits two targets with one arrow. In the present study, ferrochrome ash (FCA) obtained from the baghouse filters of ferrochrome facilities was utilized to adsorb Cu(II) for the first time in the literature. To achieve this goal, initially the FCA was characterized by XRD, XRF, SEM, EDS, and BET analyses, and then washing and grinding pretreatment was conducted to eliminate the Cr dissolution and increase the surface area of the FCA. Adsorption experiments were conducted in 100-1000 mg/L Cu(II) solution on 0.4-8 g/L FCA for 0-300 min. As a result, it was concluded that a maximum adsorption capacity was obtained as 298.75 mg/g, which makes the FCA an applicable adsorbent for Cu(II) adsorption. Additionally, a pH range of 3-6 is favorable. The Cu(II) adsorption on FCA fits the pseudo-second order (PSO) kinetics and Freundlich isotherm models well. The Cu(II)-adsorbed FCA was investigated by SEM, EDS, and FT-IR analyses. According to the results, it can be deduced that the adsorption mechanism is chemisorption, which involves the valency forces between the metal and the adsorbent.
Keywords: water treatment; ferrochrome ash; Cu(II) adsorption; adsorption kinetics; adsorption isotherms; INDUSTRIAL WASTE-WATER; HEAVY-METALS; ACTIVATED ALUMINA; COPPER IONS; II IONS; ADSORPTION; SORPTION; ADSORBENTS; FUTURE; DUST; Environmental Sciences & Ecology; Water Resources